Ingestion of a moderate dose of alcohol enhances physical exercise-induced changes in blood lactate concentration - Teixeira-Coelho,F. (2020)
The consumption of alcoholic beverages influences carbohydrate and lipid metabolism, although it is not yet clear whether metabolism during physical exercise at different intensities is also affected. This was the objective of the present study. Eight young and healthy volunteers performed a treadmill test to identify the running speed corresponding to a lactate concentration of 4 mM (S4mM). At least 48 h later, they were subjected to two experimental trials (non-alcohol or alcohol) in which they performed two 1-km running sessions at the following intensities: 1) S4mM; 2) 15% above S4mM. In both trials, blood lactate, triglycerides, and glucose concentrations were measured before and after exercise. The acute alcohol intake increased triglycerides, but not lactate concentration under resting conditions. Interestingly, alcohol intake enhanced the exercise-induced increase in lactate concentration at the two intensities: S4mM (non-alcohol: 4.2±0.3 mM vs alcohol: 4.8±0.9 mM; P=0.003) and 15% above S4mM trial (P=0.004). When volunteers ingested alcohol, triglycerides concentration remained increased after treadmill running (e.g., at S4mM - at rest; non-alcohol: 0.2±0.5 mM vs alcohol: 1.3±1.3 mM; P=0.048). In contrast, glucose concentration was not modified by either alcohol intake, exercise, or their combination. We concluded that an acute alcohol intake changed lactate and lipid metabolism without affecting blood glucose concentration. In addition, the increase in lactate concentration caused by alcohol was specifically observed when individuals exercised, whereas augmented triglycerides concentration was already observed before exercise and was sustained thereafter.